Theory of saplings growing up algorithm - Karci, Ali (Springer-Verlag Berlin, 2007)
The saplings sowing and growing up algorithm (SGA) was inspired by a natural events - evolution of growing up of trees. This algorithm contains two phases: Sowing Phase and Growing up Phase. In this paper, the theoretical foundations of SGA were determined. SGA is defined as a computational model, and it was depicted that there are a collection of Turing Machines for simulating SGA.
8th International Conference on Adaptive and Natural Computing Algorithms (ICANNGA) -- APR 11-14, 2007 -- Warsaw Univ Technol, Warsaw, POLAND